Emissions Trading Schemes under IFRS - Towards a “true and fair view” - Madlen Haupt; Roland Ismer (Climate Policy Initiative Berlin, 2011)
This research paper seeks to contribute to the latest discussions on the financial reporting for emissions trading schemes. It starts out by giving an overview of the International Financial Reporting Standards (IFRS) accounting policies, which are currently applied by the majority of participants in the EU Emissions Trading Scheme. It then argues that in order to fulfil the aims of financial reporting under IFRS, namely to provide a true and fair view, accounting must depict CO2 as a cost of production. Therefore, a fair value approach, both with respect to the initial recognition of allocated allowances and the subsequent measurement of allowances, is generally advocated. The paper finishes by highlighting the insufficiencies of the current IFRS accounting rules, which should be addressed in the upcoming new IFRS on emission trading schemes.
Keywords: Q58; L50; K34; 330; Carbon Pricing; Finance; Sustainability reporting